Carcinosarcoma of the Rectum: Report of a Rare Colorectal Malignancy and Review of the Literature - Alexis Sudlow; Ming Ho Liu; Geoffrey Waters; Vamsi R. Velchuru (Case Reports in Surgery)
Carcinosarcoma (CS) is a rare mixed mesodermal malignancy most commonly affecting the female reproductive organs, respiratory tract, head, and neck. Though infrequent, it may affect the gastrointestinal tract, most often the oesophagus and only very rarely the rectum. Histologically, it is composed of two distinct elements of epithelial and mesenchymal origin. Clinically, it is a very aggressive tumour with many patients presenting with metastatic lymph nodes or distant metastases at the time of diagnosis. Prognosis is poor despite intervention with the majority of patients dying within six months. Due to the rarity of this condition, there are no specific treatment guidelines presently available. We describe the case of an 80-year-old patient with carcinosarcoma of the rectum with discussion of the immunohistochemistry and review the available literature pertaining to this rare presentation.